Desenvolvimento e validação de metodologias para avaliação de etoricoxibe por cromatografia líquida e espectrometria de massas - Brum Junior, Liberato (2006)
Etoricoxib is a non-steroidal anti-inflammatory drug, from the coxibs group, that represents a second-generation of COX-2 inhibitors, used for the treatment of arthritis and pain. The methodologies for the evaluation of etoricoxib in pharmaceutical products and plasma were developed and validated in the present work. The reversed-phase liquid chromatography (RP-LC) analysis was carried out using a Synergi fusion C18 column (150 mm x 4.6 mm), maintained at a controlled-ambient temperature. The mobile phase consisted of phosphoric acid 0.01 M, pH 3.0/acetonitrile (62:38, V/V), run at a flow rate of 1.0 mL/min with detection at 234 nm. The chromatographic separation was obtained within 7.0 min and it was linear in the concentration range of 0.02-150 µg/mL. The liquid chromatography-tandem mass spectrometry (LC-MS/MS) method was developed and validated using a Luna C18 column (50 mm x 3.0 mm), maintained at 40 ºC and the mobile phase consisted of acetonitrile:water (95:5, V/V)/ 0.1% acetic acid (90:10, V/V), run at flow rate of 0.4 mL/min. The mass spectrometer, equipped with electrospray positive source, was used in multiple reaction monitoring mode (MRM), monitoring the transitions of 359.3>280.0 and 332.0>95.0, for etoricoxib and piroxicam (internal standard), respectively. The chromatographic separation was obtained within 2.0 min and it was linear in the concentration range of 1-5000 ng/mL. The procedures were validated evaluating parameters such as the specificity, linearity, precision, accuracy, robustness, limit of detection and limit of quantitation. Besides, for the bioanalytical method, the matrix effects, recovery and stability studies were also analyzed, giving results within the acceptable range. The proposed methods were applied for the analysis of pharmaceutical products, showing significant correlation (r=0.9999) of the results. Moreover, the liquid-liquid and solid phase extraction methods developed and optimized allowed high mean recoveries of etoricoxib and internal standard from the plasma samples. The procedures can be applied for the biovailability studies and for the quality control of pharmaceutical products.